PROVENANCE OF PINDOS FORELAND FLYSCH DEPOSITS USING SCANNING ELECTRON MICROSCOPY AND MICROANALYSIS - Vakalas, I.; Ananiadis, G.; Zelilidis, A.; Kontopoulos, N.; Tsikouras, B. (Bulletin of the Geological Society of Greece, 2004)
A number of polished thin sections from two cross sections within the Pindos foreland deposits were petrographically examined while microanalyses on certain minerals were carried out. Chemistry of these minerals is compared to analogous phases occurring in several formations in the neighbourhood of the studied areas which can stand as source areas. Our results reveal that the most probable source materials include the Pindos, Koziakas (and probably and Vourinos) ophiolite complexes, as well as metamorphic sequences of the Pelagonian Zone